2014
DOI: 10.1051/0004-6361/201424695
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude-range brightness variations of overactive K giants

Abstract: Context. Decades-long, phase-resolved photometry of overactive spotted cool stars has revealed that their long-term peak-to-peak light variations can be as large as one magnitude. Such brightness variations are too large to be solely explained by rotational modulation and/or a cyclic, or pseudo-cyclic, waxing and waning of surface spots and faculae as we see in the Sun. Aims. We study three representative, overactive spotted K giants (IL Hya, XX Tri, and DM UMa) known to exhibit V-band light variations between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 63 publications
(93 reference statements)
9
39
1
Order By: Relevance
“…Its errors are internal errors based on the root mean square (rms) of the entire time series. The above effective temperature is close to what Oláh et al (2014) obtained from VI photometry during maximum photometric brightness, but the metallicity differs by a factor of two.…”
Section: +032supporting
confidence: 84%
See 4 more Smart Citations
“…Its errors are internal errors based on the root mean square (rms) of the entire time series. The above effective temperature is close to what Oláh et al (2014) obtained from VI photometry during maximum photometric brightness, but the metallicity differs by a factor of two.…”
Section: +032supporting
confidence: 84%
“…We took interstellar absorption into account with 0. m 1 per 100 pc (Strassmeier 1999). We note that Oláh et al (2014) estimated the reddening of XX Tri from all-sky infrared imaging and found a color excess…”
Section: +032mentioning
confidence: 83%
See 3 more Smart Citations